Do the stock returns of clean energy corporations respond to oil price shocks and policy uncertainty? - Xiaohui Zhao (Journal of Economic Structures, 2020)
This paper investigates the effects of oil price shocks and policy uncertainty on the stock returns of clean energy companies. We use a structural vector autoregressive (VAR) model to separate demand and supply shocks in the global crude oil market from 2001 to 2018. We find that oil supply shocks and aggregated demand shocks have a positive effect on the returns of clean energy companies, while policy uncertainty shocks and oil-specific-demand shocks have a negative effect. The impacts of these shocks are shown to last relatively long. Moreover, the effects of oil shocks on the clean energy stock returns are amplified by adding policy uncertainty as an endogenously driven factor to the model. The impact of policy uncertainty is mainly transmitted through the uncertainty of inflation.
Keywords: 330; Oil price shocks; Policy uncertainty; Clean energy companies; Stock market